1974
DOI: 10.1073/pnas.71.7.2595
|View full text |Cite
|
Sign up to set email alerts
|

Target Cell Polarity and Membrane Phosphorylation in Relation to the Mechanism of Action of Antidiuretic Hormone

Abstract: The plasma membrane of the bovine renal collecting duct epithelial cell has been resolved into its apical (luminal) and basal-lateral (contraluminal) components by free flow electr4iphoresis. The contraluminal, but not the luminal, membrane was found to contain antidiuretic hormone-sensitive adenylate cyclase. The luminal membrane was found to contain a cyclic 3': 5'-adenosine monophosphate-sensitive self-phosphorylating system consisting of a membrane-bound protein kinase and its membrane-bound substrate(s); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

1976
1976
1999
1999

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(16 citation statements)
references
References 30 publications
0
14
0
2
Order By: Relevance
“…At least one previous study, in which no AVP-sensitive adenylyl cyclase was detected in the luminal membrane fraction of the bovine collecting duct, appears to argue against the possibility that the inhibition is related to an increase in cyclic AMP by luminal AVP (42). As mentioned earlier, nanomolar AVP is capable ofautoinhibiting the hydroosmotic effect through activation of protein kinase C, elevation of the intracellular free Ca"+ concentration, or stimulation of prostaglandin synthesis (1).…”
Section: Test)mentioning
confidence: 93%
“…At least one previous study, in which no AVP-sensitive adenylyl cyclase was detected in the luminal membrane fraction of the bovine collecting duct, appears to argue against the possibility that the inhibition is related to an increase in cyclic AMP by luminal AVP (42). As mentioned earlier, nanomolar AVP is capable ofautoinhibiting the hydroosmotic effect through activation of protein kinase C, elevation of the intracellular free Ca"+ concentration, or stimulation of prostaglandin synthesis (1).…”
Section: Test)mentioning
confidence: 93%
“…It is tempting to speculate that epithelial H + transport occurs through a proton-translocating ATPase. Recently, it had been demonstrated that "HCOa-stimulated" ATPases are present in the gastric mucosa (14) and in luminal membranes of the renal tubule (20) and turtle bladder (4). The mitochondrial and bacterial "HCOa-stimulated" ATPase is the locus of H + transport (9,17,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…In four paired hemibladders bathed with Ringer's solution at pH 7.4 and short-circuited, the initial rate of H+ transport in the control bladder was 2.6 nmol/min cm2 and in the bladder to receive DCCD it was 3.6 nmol/min cm2. Exposure of the luminal surface to 0.2 mM DCCD for 15 min caused complete inhibition of H+ transport. The resistance of the bladder increased from 3369 ± 451 ohms/cm2 before treatment with DCCD to 3504 ± 431 ohms/cm2 after exposure to DCCD.…”
Section: Resultsmentioning
confidence: 99%